Bisphenol a exposure in Mexico City and risk of prematurity: a pilot nested case control study - Mercado-García Adriana; Lamadrid-Figueroa Héctor; Sánchez Brisa N; Hu Howard; Meeker John D; Cantonwine David; Fortenberry Gamola Z; Calafat Antonia M; Téllez-Rojo Martha (BMC, 2010)
Abstract Background Presence of Bisphenol A (BPA) has been documented worldwide in a variety of human biological samples. There is growing evidence that low level BPA exposure may impact placental tissue development and thyroid function in humans. The aim of this present pilot study was to determine urinary concentrations of BPA during the last trimester of pregnancy among a small subset of women in Mexico City, Mexico and relate these concentrations to risk of delivering prematurely. Methods A nested case-control subset of 60 participants in the Early Life Exposure in Mexico to ENvironmental Toxicants (ELEMENT) study in Mexico City, Mexico were selected based on delivering less than or equal to 37 weeks of gestation and greater than 37 weeks of gestation. Third trimester archived spot urine samples were analyzed by online solid phase extraction coupled with high performance liquid chromatography isotope dilution tandem mass spectrometry. Results BPA was detected in 80.0% (N = 48) of the urine samples; total concentrations ranged from < 0.4 μg/L to 6.7 μg/L; uncorrected geometric mean was 1.52 μg/L. The adjusted odds ratio of delivering less than or equal to 37 weeks in relation to specific gravity adjusted third trimester BPA concentration was 1.91 (95%CI 0.93, 3.91, p-value = 0.08). When cases were further restricted to births occurring prior to the 37th week (n = 12), the odds ratio for specific-gravity adjusted BPA was larger and statistically significant (p < 0.05). Conclusions This is the first study to document measurable levels of BPA in the urine of a population of Mexican women. This study also provides preliminary evidence, based on a single spot urine sample collected during the third trimester, that pregnant women who delivered less than or equal to 37 weeks of gestation and prematurely (< 37 weeks) had higher urinary concentrations of BPA compared to women delivering after 37 weeks.